2012
DOI: 10.1021/jp301193r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis of Solid Electrolytes: Preparation, Characterization, and Li Ion Transport Properties of Garnet-Type Al-Doped Li7La3Zr2O12 Crystallizing with Cubic Symmetry

Abstract: Various polycrystalline samples of Al-doped garnet-like Li 7 La 3 Zr 2 O 12 crystallizing with cubic symmetry were synthesized from the binary oxides Li 2 O, ZrO 2 , Al 2 O 3 , and La 2 O 3 . The synthesis of phase pure samples was carried out following a two-step preparation route. It consists of an activation step by high-energy ball milling and a subsequent annealing step at elevated temperatures. The synthesis route chosen allows the precise adjustment of the cationic ratios, leading to a garnet which is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 45 publications
7
131
2
Order By: Relevance
“…LLZ [12] while the line with a larger chemical shift value might be related to the replacement of La and Zr by Al [19]. Most likely, Al resides on a tetrahedral site near a La or Zr vacancy.…”
Section: Al and 6 LI Mas Nmr Spectramentioning
confidence: 99%
“…LLZ [12] while the line with a larger chemical shift value might be related to the replacement of La and Zr by Al [19]. Most likely, Al resides on a tetrahedral site near a La or Zr vacancy.…”
Section: Al and 6 LI Mas Nmr Spectramentioning
confidence: 99%
“…39 Duvel et al prepared Al-doped LLZrO samples by a mechanochemical route and discovered that with increasing Al content, Al ions can also substitute at non-Li cation sites, leading to the formation of La-and Zr-deficient LLZrO. 40 Huang et al indicated a similar effect for Ge-doped LLZrO, according to a comparison of their experimental and simulated XANES spectra. 41 Recently, Ga-doped cubic LLZrO was successfully prepared by standard solid state synthesis 42−44 and a low-temperature sol gel approach.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reports indicated that the unintentional incorporation of Al 3+ from alumina crucibles during the high-temperature solid state synthesis helps to stabilize the cubic phase against the tetragonal one. [12][13][14][15] The inclusion of Al 2 O 3 from alumina crucible during the preparation of lithium garnets at high sintering temperature around 1225 • C is inevitable. However it is not known completely whether the included Al 3+ occupies the Li + sites or an interstitial site.…”
Section: Introductionmentioning
confidence: 99%